Policy Interest Rate, Risk Management and Profitability: Study Of Public Listed Banks in ASEAN Countries - Gracia S. Ugut; Liza Handoko (Lembaga Publikasi Ilmiah Nusantara, 2026)
The paper aims to explore the impact of low interest rate policy and prudent behavior on the profitability of ASEAN-4 publicly listed banks. The study uses net interest margin as a measure of profitability because it reflects a bank's ability to manage its operations and interest-bearing assets effectively. A panel data regression model is used to analyze data from 79 publicly listed banks in ASEAN-4 countries (Thailand, Indonesia, the Philippines, and Malaysia) from 2005 to 2019. There are three variables for risk management: the capital adequacy ratio (CAD), which measures the prudential approach to risk management; the asymmetric Z-score, an accounting measure of insolvency risk; and the volatility of net interest income. The study also includes two control variables: bank control variables (equity, size, and lending) and Country control variables (real GDP and average inflation). The model employs General Method of Moments (GMM) estimators to mitigate potential endogeneity issues in the panel data regression. The interaction terms of prudential behavior and the interest rates are negative and significant for the Z-score; positive and significant for the volatility of NIM and the capital adequacy ratio. Therefore, the profitability of banks and interest rates are more closely related when banks' risk management policies and practices are better managed.